Analisis perbedaan kinerja keuangan perusahaan perbankan (yang masuk kelompok lq45 dengan yang tidak masuk kelompok lq45) yang terdaftar di bei tahun 2016 - 2018 - Willem, Willem; Mahrawati, Mahrawati; Lite, Lite; Fransiska, Robert (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the financial differences between banking companies that are included in the LQ45 group and banking companies that are not included in the LQ45 group listed on the Indonesia Stock Exchange (IDX) in 2016 – 2018. This study uses a quantitative approach. different test analysis techniques T-Test and Mann-Whitney Test. The results show that from the aspect of Return On Equity (ROE), Return On Assets (ROA) and Net Profit Margin (NPM). There are differences in financial performance between banking companies that fall into the LQ45 group and banking companies that do not enter the LQ45 group that listed on the Indonesia Stock Exchange (IDX) in 2016 – 2018. Based on the results of this study, it is recommended to investors or potential investors that in making decisions they take into account aspects of Return On Equity (ROE), Return On Assets (ROA) and Net Profit Margin (NPM). ) ) company, variables and other relevant information. The limitation of this study is that the sample only consists of banking companies that are included in and not included in the LQ45 group, the research period is relatively short, only three years. In this study, it is suggested to expand the object and research variables, with a longer period of time, so as to obtain more accurate and comprehensive results.